2017
DOI: 10.1149/07704.0127ecst
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Etch Pits on Germanium Surfaces Loaded with Reduced Graphene Oxide in Water

Abstract: Graphene oxide (GO) was reduced by either a thermal treatment in Ar ambient or a chemical process using hydrazine monohydrate. A Ge surface loaded with reduced GO (RGO) was immersed in water containing dissolved O 2 molecules. We demonstrated that etch pits were formed by the immersion, whose shape depended on the initial form (particles or dispersed sheets) of RGO on Ge. We speculate that a Ge surface in contact with RGO is selectively etched in water by the catalytic activity of RGO, which enhances the oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Nakade et al 192 investigated the use of highly-reduced graphene oxide (hrGO) as a catalyst for the MacEtch of Ge. As metal catalysts can induce surface contamination, it was suggested that a graphene oxide catalyst would allow for surface flattening via a MacEtch process without the presence of metal catalysts.…”
Section: Germaniummentioning
confidence: 99%
See 2 more Smart Citations
“…Nakade et al 192 investigated the use of highly-reduced graphene oxide (hrGO) as a catalyst for the MacEtch of Ge. As metal catalysts can induce surface contamination, it was suggested that a graphene oxide catalyst would allow for surface flattening via a MacEtch process without the presence of metal catalysts.…”
Section: Germaniummentioning
confidence: 99%
“…191 MacEtch of Ge substrates, which are otherwise easily damaged by many commonly used surface chemistries, may provide a means to take advantage of the attributes of Ge without confronting the issues associated with Ge surface processing. Novel approaches to Ge MacEtch have been adopted by utilizing gentle wet chemistries for catalytic etching (e.g., use of H 2 O as the primary etchant), or the employment of novel catalysts such as various reduced states of graphene, 192,193 which is intriguing as graphene is a promising next generation material for a range of devices. 194,195 Ge MacEtch results are tabulated in Table 7.…”
Section: Germaniummentioning
confidence: 99%
See 1 more Smart Citation
“…explored Si etching by using carbon allotropes such as nanotubes and nanospheres in a HF/H 2 O vapor . In our recent study, we demonstrated that the Ge surface under single sheets of reduced graphene oxide (rGO) was preferentially etched in O 2 -containing water. , Chemically modified graphene including rGO has a unique feature that allows it to be dispersed in liquid. Owing to this feature, chemical etching enhanced by a modified graphene sheet is compatible with conventional wet processes such as spray coating and lithography to form a three-dimensional structure on a semiconductor surface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al [15] investigated the formation of Ge nanostructures by wet etching assisted by graphene. Nakade et al [16,17] employed reduced graphene oxide to boost Ge wet etching in water. However, graphene-and graphene oxide-assisted chemical etching of Ge suffer from low etch rate (20-30 nm h −1 even when heated up) and poor morphologies, which make it unsuitable for mass production of uniform nanostructures.…”
mentioning
confidence: 99%